Grenada : Request for Disbursement Under the Rapid Credit Facility; Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Grenada. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Grenada's Request for Disbursement Under the Rapid Credit Facility. IMF financing support provides resources to the countries' authorities for essential health-related expenditures and income support to ease the impact of coronavirus disease 2019 on the population. The countries' governments have responded to the pandemic by swiftly implementing containment measures, allocating scarce budgetary resources to critical health care spending, and introducing income support to the most affected sectors and households. Protection of the financial system will help cushion the economic impact of the pandemic. Measures have also been taken by the Eastern Caribbean Central Bank to facilitate the provision of credit and safeguard financial stability. Going forward, and once the current crisis dissipates, the authorities intend to push ahead with a comprehensive Disaster Resilience Strategy aimed at building resilience to natural disasters. They are also committed to further strengthening financial sector oversight to safeguard macro-financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet